Gulp: Adventures on the Alimentary Canal - Mary Roach (Oneworld Book, 2013)
Eating is the most pleasurable, gross, necessary, unspeakable biological process we humans undertake. But very few of us realise what strange wet miracles of science operate inside us after every meal - let alone have pondered the results (of the research). How have physicists made crisps crispier? What do laundry detergent and saliva have in common? Was self-styled \'nutritional economist\' Horace Fletcher right to persuade millions of people that chewing a bite of shallot 700 times would yield double the vitamins? And did Elvis actually die from constipation? In her trademark, laugh-out-loud style, Mary Roach breaks bread with spit connoisseurs and enema exorcists, stomach slugs, rectum-examining prison guards, and competitive hot dog eaters as she investigates the beginning - and the end - of our food.